2016
DOI: 10.1103/physrevb.93.115103
|View full text |Cite
|
Sign up to set email alerts
|

Boson condensation in topologically ordered quantum liquids

Abstract: Boson condensation in topological quantum field theories (TQFT) has been previously investigated through the formalism of Frobenius algebras and the use of vertex lifting coefficients. While general, this formalism is physically opaque and computationally arduous: analyses of TQFT condensation are practically performed on a case by case basis and for very simple theories only, mostly not using the Frobenius algebra formalism. In this paper we provide a new way of treating boson condensation that is computation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
82
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(83 citation statements)
references
References 100 publications
(146 reference statements)
1
82
0
Order By: Relevance
“…This anyon condensation [42][43][44] procedure effectively glues the two FTI slabs together along the TR symmetric surfaces (see Fig. 1).…”
Section: Gluing T-pfaffian* Surfacesmentioning
confidence: 99%
“…This anyon condensation [42][43][44] procedure effectively glues the two FTI slabs together along the TR symmetric surfaces (see Fig. 1).…”
Section: Gluing T-pfaffian* Surfacesmentioning
confidence: 99%
“…The self-bosons that condense in B transform into the trivial boson 1 ∈ B ′ , when they cross the GWD. The connection between GDWs in bTOs and self-boson condensation has been thoroughly studied recently [16,17,[24][25][26][27][28][29][30]. It has been found that GDWs between bosonic topological orders can be classified by anyon condensation [16,17].…”
Section: Jhep03(2017)172mentioning
confidence: 99%
“…For a TNS that describes a topologically ordered wave function in 2D, the gauge symmetry of local tensors is necessary [29]; i.e., each local tensor should be invariant under local symmetry transformations on virtual legs. For a gauge-symmetric TNS, we are able to compute modular matrices [20][21][22] which can detect topological phase transitions [30][31][32].…”
Section: Introductionmentioning
confidence: 99%